A Comparative Study on Modified Lecture and Self-Instructional Module on Students’ Emotional Intelligence and Academic Performance at Colleges of Nursing Abuja, Nigeria - Tsiamu Juliana (WORLD JOURNAL OF INNOVATION AND MODERN TECHNOLOGY, 2026)
Background: Modified lecture and self-instructional module can help students develop skills needed to thrive in a fast-paced academic world, particularly in relation to emotional intelligence and academic performance. However, there is no clear evidence about which method is more effective at improving nursing students’ emotional intelligence and academic performance, creating a challenge in nursing education. To address this, the study compares modified lecture and self-instructional module on students’ emotional intelligence and academic performance at Colleges of Nursing in Abuja. Research Method: A non-equivalent quasi-experimental design was used with purposive sampling, selecting 210 second-year basic nursing students as participants. Data were analyzed through frequencies, percentages, mean scores, analysis of covariance and independent sample t tests, at 0.05 significant alpha level. Results: The findings of this study revealed that students in modified lecture group had a higher score of emotional intelligence in both phases (before = 2.71/5±1.05; after = 2.83/5±1.09) compared to self-instructional module (before = 2.60/5±1.08; after = 2.35/5±1.15) and that both modified lecture (ML=24.99/31±3.89 and self-instructional module (SIM=24.81/31±3.81) groups had a positive effect on students’ academic performance. Statistically, there was a strong significant (p